2015
DOI: 10.3168/jds.2015-9593
|View full text |Cite
|
Sign up to set email alerts
|

Effects of space allowance on the behavior and physiology of cattle temporarily managed on rubber mats

Abstract: Dairy cattle managed in some pasture-based systems, such as in New Zealand, are predominantly kept outdoors all year around but are taken off pasture for periods, especially in wet weather to avoid soil damage. The use of rubber matting for such stand-off practices is becoming more common to improve animal welfare, and our objective was to investigate the effects of different space allowances on cow behavior and physiology when managed temporarily on rubber mats during a weather-induced stand-off period. Thirt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 41 publications
2
17
0
Order By: Relevance
“…Cows that were on the wet surface showed clear compensatory lying behavior when they were on pasture, both after the daily exposure and after the 5-d treatment period, thus indicating that even a short-term reduction in lying time will alter the motivation for lying for several days. The same pattern of rebound behavior has been seen in other studies where dairy cattle are temporarily managed on hard and muddy surfaces (Fisher et al, 2003;Schütz and Cox, 2014), on rubber matting at high stocking densities (Schütz et al, 2015), and after periods of deprivation (Tucker et al, 2018). The collected evidence suggests that cows will give up feeding to compensate for previous, inadequate rest on uncomfortable or otherwise unsuitable conditions.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…Cows that were on the wet surface showed clear compensatory lying behavior when they were on pasture, both after the daily exposure and after the 5-d treatment period, thus indicating that even a short-term reduction in lying time will alter the motivation for lying for several days. The same pattern of rebound behavior has been seen in other studies where dairy cattle are temporarily managed on hard and muddy surfaces (Fisher et al, 2003;Schütz and Cox, 2014), on rubber matting at high stocking densities (Schütz et al, 2015), and after periods of deprivation (Tucker et al, 2018). The collected evidence suggests that cows will give up feeding to compensate for previous, inadequate rest on uncomfortable or otherwise unsuitable conditions.…”
Section: Discussionsupporting
confidence: 70%
“…In a study simulating a 4-d stand-off period in New Zealand, nonlactating cows spent 41 and 47% less time lying when managed on a concrete or a muddy surface (small paddock and race laneway), respectively, compared with a well-drained wood chip surface (Fisher et al, 2003). Cattle with reduced lying times during the stand-off period will spend more time lying on pasture when they are allowed their daily feed allowance (Fisher et al, 2003;Schütz and Cox 2014;Schütz et al, 2015), a time where, ideally, they should be grazing. In addition, wet underfoot conditions are a contributing factor to softer hooves and therefore a greater risk for claw lesions and lameness (Williams et al, 1986;Jubb and Malmo, 1991;Borderas et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…As daily lying time on the pad decreased, cows lay down more when in the paddock, a consistent response even with shorter periods of stand-off than those used in this study [11,32], Schütz [38] determined that cows that are not able to lie down for a sufficient amount of time during the stand-off period will try to compensate by lying down more when they are at pasture, a time when they ideally should be grazing. Although the cows in this study did not have the high energy requirements associated with lactation, they were in late pregnancy, and it is unclear whether less than 6 h of grazing per day is sufficient to meet their daily energy requirements.…”
Section: Discussionsupporting
confidence: 57%
“…These heifers also had a higher frequency of allogrooming, but showed no difference in the frequency of agonistic interactions. Schütz et al (121) reported that a minimum of 6 m 2 of space allowance per cow was needed on an off-wintering rubber pad during an 18 h stand off period to maintain daily lying times similar to that observed when cows were housed on pasture. When cows were provided less space (3 or 4.5 m 2 /cow), the reduction in both lying time and lying bout duration and frequency was thought to be due to increased agonistic behavior.…”
Section: Social Behaviormentioning
confidence: 90%